Optimizing EFL Education: A Boarding Language Program Management Model for Indonesian Islamic University Students - Sari Famularsih; Ari Setiawan; Alfin Rosyidha; Binti Muflikah; Umi Aisyah Sulistyaning Tyas; Safinatul Fitriah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This research investigates the development of an educational management model for a Boarding Language Program (BLP) designed to enhance the language competencies of advanced English as a Foreign Language (EFL) learners at the State Islamic University in Salatiga, Indonesia. The study aims to (1) analyze the learners’ language skill profiles before joining the program, (2) propose a comprehensive management model encompassing curriculum, infrastructure, and student admissions, and (3) evaluate the model’s acceptability and effectiveness. Method: A mixed-methods approach combining qualitative and quantitative data collection, including observations, interviews, and assessments. Results: Results indicate that the BLP significantly improves language proficiency while fostering immersive, interactive learning experiences. The development model on educational management of boarding language programs on language aspects for advanced English as a Foreign Language (EFL) learners is adequate or acceptable in improving learners’ language skills based on the result of the Wilcoxon test. Novelty: Findings suggest that the BLP offers significant potential for improving language skills and preparing students for global competitiveness, providing a replicable framework for other educational institutions.